Correlation between Body Mass Index, Gender, and Skeletal Muscle Mass Cut off Point in Bandung - Wattimena, Richi Hendrik; Vitriana, Vitriana; Devi, Irma Ruslina (International Journal of Integrated Health Sciences, 2017)
Objective: To determine the average skeletal muscle mass (SMM) value in young adults as a reference population; to analyze the correlation of gender, and body mass index to the cut off point; and to determine skeletal muscle mass cut off points of population in Bandung, Indonesia.Methods: This was a cross-sectional study involving 199 participants, 122 females and 77 males. The sampling technique used was the multistage random sampling. The participants were those who lived in four major regions in Bandung, Indonesia: Sukajadi, Cicadas, Buah Batu, and Cibaduyut. Results: The average appendicular skeletal mass index (ASMI) in females and males based on body mass index (BMI) were identified. The average ASMI values for normal BMI in females was 5.982±0.462 kg/m2 while the average ASMI values normal BMI for males was 7.581±0.744 kg/m2Conclusions: A correlation between BMI and ASMI that was considered statistically significant was found in females (0.7712; p<0.05) and a very significant correlation was seen in males (0.870; p<0.05). The cut off points were defined by the normal BMI, which were 5.059 for females and 6.093 for males. Keywords: Appendicular skeletal muscle mass index, body mass index, cut off point, gender, skeletal muscle mass DOI: 10.15850/ijihs.v5n2.990